2012
DOI: 10.1002/arch.21039
|View full text |Cite
|
Sign up to set email alerts
|

A DIGESTIVE LIPASE OF Pieris brassicae L. (LEPIDOPTERA: PIERIDAE): PURIFICATION, CHARACTERIZATION, AND HOST PLANTS EFFECTS

Abstract: The properties of a digestive lipase from the larval midgut of Pieris brassicae were studied by performing biochemical purification, characterization, effect of host plants, and extracted inhibitors. The purification process revealed a lipase with a purification fold of 42, recovery of 18.12%, molecular weight mass of 72.3 kDa, optimal pH at 11, and optimal temperature at 30°C, as well as stability at the optimal temperature for 12 h. The purified enzyme was inhibited by the ions Na(+), Mn(+), Fe(2+), and Cu(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Zibaee and Fazeli-Dinan (2012) purified a digestive lipase in the midgut of N. aenescens with a molecular weight of 51 kDa. Zibaee (2012) found that the fourth instar larvae of P. brassicae have a digestive lipase with a molecular weight of 72.3 kDa. Orscelk et al (2007) found a total body lipase of Gryllus campestris L. (Orthoptera: Gryllidae) with a molecular mass of 76.5 kDa.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Zibaee and Fazeli-Dinan (2012) purified a digestive lipase in the midgut of N. aenescens with a molecular weight of 51 kDa. Zibaee (2012) found that the fourth instar larvae of P. brassicae have a digestive lipase with a molecular weight of 72.3 kDa. Orscelk et al (2007) found a total body lipase of Gryllus campestris L. (Orthoptera: Gryllidae) with a molecular mass of 76.5 kDa.…”
Section: Discussionmentioning
confidence: 98%
“…Zibaee and Fazeli-Dinan (2012) found an optimal pH of 10 and temperature of 35-40°C for a lipase in the larvae of Naranga aenescens. Zibaee (2012) reported an optimal pH of 8 and 10 for digestive soluble-and membrane-bound lipase in the midgut of Pieris brassicae L. (Lepidoptera: Pieridae). In an unpublished study, optimal pH and temperature for activity of the purified lipase in the midgut of E. integriceps was obtained to be 7 and 25-30°C.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations